2011
DOI: 10.1111/j.1748-1716.2010.02248.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive dietary potassium supplementation in young salt-sensitive Dahl rats attenuates development of salt hypertension by decreasing sympathetic vasoconstriction

Abstract: The attenuation of enhanced sympathetic vasoconstriction is the principal mechanism of antihypertensive action exerted by preventive potassium supplementation in immature Dahl rats. Dietary potassium supplementation has no preventive effects on BP in adult salt-loaded animals or no therapeutic effects on established salt hypertension in young rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
0
10
1
1
Order By: Relevance
“…is responsible for development and progression of hypertension, renal damage and other complications [1,6,19]. On the other hand, several studies have reported that potassium supplementation decreased sodium retention and moderates the ''water logging'' in the vascular system, and thereby hypertension amelioration [2,6,19,22]. Notably, we found that antihypertensive activity of EO was also associated with decreased serum Na ?…”
Section: Discussionmentioning
confidence: 53%
“…is responsible for development and progression of hypertension, renal damage and other complications [1,6,19]. On the other hand, several studies have reported that potassium supplementation decreased sodium retention and moderates the ''water logging'' in the vascular system, and thereby hypertension amelioration [2,6,19,22]. Notably, we found that antihypertensive activity of EO was also associated with decreased serum Na ?…”
Section: Discussionmentioning
confidence: 53%
“…In contrast, magnesium deficiency aggravated the insulin resistance produced by high fat diets given to growing rats [ 34 ]. None of the other major minerals in the seaweeds such as potassium, calcium and zinc were present in sufficient quantities to have bioactive effects on the metabolic syndrome [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our chronic experiments in Dahl rats provided several interesting findings concerning age-dependent effects of various antihypertensive interventions. Thus, dietary potassium supplementation attenuated salt hypertension development only in young but not in adult DS animals and this effect was mediated by a reduction of sympathetic vasoconstriction (Zicha et al 2011). Similarly, dietary calcium supplementation diminished hypertension development in young DS rats, whereas the same high-calcium diet enhanced salt hypertension development in adult DS animals (Kuneš et al 1988).…”
Section: Discussionmentioning
confidence: 99%